Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1146/annurev-micro-050323-040543
|View full text |Cite
|
Sign up to set email alerts
|

Versatility and Complexity: Common and Uncommon Facets of LysR-Type Transcriptional Regulators

Abstract: LysR-type transcriptional regulators (LTTRs) form one of the largest families of bacterial regulators. They are widely distributed and contribute to all aspects of metabolism and physiology. Most are homotetramers, with each subunit composed of an N-terminal DNA-binding domain followed by a long helix connecting to an effector-binding domain. LTTRs typically bind DNA in the presence or absence of a small-molecule ligand (effector). In response to cellular signals, conformational changes alter DNA interactions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 136 publications
(216 reference statements)
0
3
0
Order By: Relevance
“…LTTR family members typically consist of a N-terminal DNA-binding domain and a C-terminal ligand-binding domain (LBD). Typically, ligand binding modulates the regulatory activity of LTTRs ( 49 ). Previous data in E. coli revealed that 4HBA, salicylate, and benzoate induce aaeXAB expression ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…LTTR family members typically consist of a N-terminal DNA-binding domain and a C-terminal ligand-binding domain (LBD). Typically, ligand binding modulates the regulatory activity of LTTRs ( 49 ). Previous data in E. coli revealed that 4HBA, salicylate, and benzoate induce aaeXAB expression ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the large impact of LsrB on beta‐lactam resistance by directly modulating the levels of the anhydroamidase AmpD, we wondered how LsrB itself is regulated. A hallmark of LysR‐type transcription factors is their autoregulation (Baugh et al., 2023; Maddocks & Oyston, 2008). In Rhizobiaceae , including Agrobacterium , LsrB is encoded in a conserved operon downstream of trxB coding for a thioredoxin reductase (Budnick et al., 2020; Eisfeld et al., 2021; Luo et al., 2005; Sheehan et al., 2015; Sheehan & Caswell, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that the bidirectional promoter shared by ampC and ampR is regulated by AmpR itself. This type of autoregulation is very common for LysR‐type transcription factors (Baugh et al., 2023; Maddocks & Oyston, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…The diversity and complexity of LTTRs in K. pneumoniae highlight their importance in adapting and surviving in different environments, including their ability to colonize and infect humans. Proteins bind to specific regions of DNA known as regulator binding sites (RBSs) and can function as either activators or repressors of gene transcription [ 148 ]. A study conducted in K. pneumoniae investigated the Type VI Secretion System (T6SS) factor, which is associated with cell invasion, competition, and colonization processes.…”
Section: Transcriptional Regulation and Cryptic Resistance Mechanismsmentioning
confidence: 99%